Removal of a cationic dye from wastewaters by adsorption on activated carbon developed from coconut coir - Sharma Y.C.; Uma; Upadhyay S.N. (My University, 2025)
Biosorption of a cationic dye, methylene blue (MB) onto coconut coir activated carbon (CCAC) developed by thermal activation has been investigated. Coconut coir is a byproduct of Coconut based industries. The unusable part of the coconut coir was used to develop activated carbon. The effect of contact time and temperature on the removal of dye was studied. The process of dye removal followed a first-order kinetics, and the value of the rate constant of adsorption was found to be 1.15 × 10-2 min-1 under optimum conditions. Adsorption data was fitted to Langmuir, Freundlich, Temkin, and Dubinin-Radushkevich adsorption isotherm equations. The thermodynamic studies for the process of removal of dye were carried out, and the parameters, namely, free energy (ΔG°), enthalpy (ΔH°), and entropy (ΔS°) changes, were determined. The removal increased from 74.20 to 93.58% with decrease in concentration of dye from 100 to 60 mg/L at 30 °C, 150 rpm, and pH 5.3. The removal exhibited an increasing trend with increasing temperature, exhibiting the endothermic nature of the removal process. © 2009 American Chemical Society.